2005
DOI: 10.1246/bcsj.78.1401
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Aryl- and Alkyl-bis(trifluoromethylsulfonyl)methanes

Abstract: Various arylbis(trifluoromethylsulfonyl)methanes (1) have been synthesized by reacting the corresponding benzylic halides with sodium trifluoromethanesulfinate and then with triflic anhydride. In addition, when the aryl group of 1 is a pentafluorophenyl group, the nucleophilic para-substitution of the aryl group with alkyllithiums and sodium alkoxides occurs. This reaction is useful for the design of new Brønsted acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…[5,6] The aryl-substituted derivatives, which are depicted as Tf 2 CHAr, may be prepared by a stepwise procedure through the nucleophilic substitution of reactive benzylic halides by NaOS(O)CF 3 and the following a-triflylation of the resulting monosulfone compounds by using tBuLi and Tf 2 O. [7] We also reported that 1,1,3,3-tetrakis(trifluoromethanesulfonyl)propane 1 (Tf 2 CHCH 2 CHTf 2 ) performs as one of the most effective Brønsted acid pre-catalysts for CÀC bond forming reactions using silylated nucleophiles. [8,9] This compound can be prepared by the reaction of Tf 2 CH 2 with paraformaldehyde on a multi-gram scale (Scheme 1).…”
mentioning
confidence: 99%
“…[5,6] The aryl-substituted derivatives, which are depicted as Tf 2 CHAr, may be prepared by a stepwise procedure through the nucleophilic substitution of reactive benzylic halides by NaOS(O)CF 3 and the following a-triflylation of the resulting monosulfone compounds by using tBuLi and Tf 2 O. [7] We also reported that 1,1,3,3-tetrakis(trifluoromethanesulfonyl)propane 1 (Tf 2 CHCH 2 CHTf 2 ) performs as one of the most effective Brønsted acid pre-catalysts for CÀC bond forming reactions using silylated nucleophiles. [8,9] This compound can be prepared by the reaction of Tf 2 CH 2 with paraformaldehyde on a multi-gram scale (Scheme 1).…”
mentioning
confidence: 99%
“…Preparation of (m,p-substituted phenyl)methyl trifluoromethyl sulfones (1). 31 General procedure: A mixture of benzylic halide (10 mmol) and CF 3 SO 2 Na (2.0 g, 13 mmol) in propionitrile (30 mL) was heated at reflux temperature. While disappearance of the starting halide was monitored by TLC, the mixture was cooled, the salts were removed by filtration and the filtrate was concentrated under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…31 General procedure: To a solution of 1 (0.5 mmol) in dry diethyl ether (3 mL) was added t-BuLi (0.34 mL, 0.55 mmol, 1.6 M solution in hexane) dropwise at ¹78°C, and the resulting mixture was stirred for 20 min. Triflic anhydride (92 mL, 0.28 mmol) was then added, and the resulting mixture was allowed to warm to room temperature over a period of 1 h. After the reaction mixture was cooled to ¹78°C, t-BuLi (0.34 mL, 0.55 mmol, 1.6 M in hexane) was added dropwise, and the resulting mixture was stirred for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…5 In addition, although many excellent ligands have been developed for different substrates, 5 these procedures suffer from lack of generality. Diaryl-substituted planar frameworks such as naphthalene, [9][10][11][12][13] biphenylene, 14,15 dibenzothiophene, 16 dibenzofuran 15 and xanthene 15,17 have fascinating scaffolds with unusual geometry in organic molecules. The two aryl units bonded to planar frameworks in sufficiently close positions provide a parallel faceto-face arrangement, thus indicating - interactions that play an important role in a variety of chemical properties such as molecular recognition, 18 stereocontrolled reactions, 19 protein and nucleic acid structures, 20 and crystal packing.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8]14,15 We recently reported that aryltriolborates, which have good stability in air-and water, undergo very smooth and fast transmetalation to various transition metal complexes. The utility of these tetra-coordinated arylboron compounds has already been demonstrated in palladium-catalyzed cross-coupling, 22,23 coppercatalyzed N-arylation of amines 24 and rhodium-catalyzed 1,4-addition to enones.…”
Section: Introductionmentioning
confidence: 99%